K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Choose a verb in column A with a preposition in column B to make a phrasal verb to complete the sentence:Column AColumn Bwear, turn, wrap, break, go, run, come, cheat, hear, payup, off, on, into, out, for, down, in, around, from1. Someone called my name, and I ................. to see who it was.2. Janice ................... one problem after another at work yesterday.3. He pulled and pulled, but the blowing ball did not ............................4. We haven't ....................... Linda...
Đọc tiếp

Choose a verb in column A with a preposition in column B to make a phrasal verb to complete the sentence:

Column AColumn B
wear, turn, wrap, break, go, run, come, cheat, hear, payup, off, on, into, out, for, down, in, around, from

1. Someone called my name, and I ................. to see who it was.

2. Janice ................... one problem after another at work yesterday.

3. He pulled and pulled, but the blowing ball did not ............................

4. We haven't ....................... Linda for ages.

5. I don't really .............. for wiinter sports very much.

6. The principal told me you'd been ..................... the test.

7. They should be ...................... the meeting in a few minutes.

8. Young people think that drugs are harmless, but they'll ................... their foolishness someday.

9. After he started drinking heavily, their marriage stared to ..................

10. People who live in the city ....................... their car braked faster than people who live in the countryside.

 

0

(x+5)3-x3-125

=x3+53-x3-53

=0

21 tháng 8 2020

1. \(\left(x+5\right)^3-x^3-125\)

\(=x^3+15x^2+75x+125-x^3-125\)

\(=15x^2+75x\)

2. \(x^3+6x^2+12x+8=0\)

\(\Leftrightarrow x^3+2x^2+4x^2+8x+4x+8=0\)

\(\Leftrightarrow x^2\left(x+2\right)+4x\left(x+2\right)+4\left(x+2\right)=0\)

\(\Leftrightarrow\left(x^2+4x+4\right)\left(x+2\right)=0\)

\(\Leftrightarrow\left(x+2\right)^2\left(x+2\right)=0\)

\(\Leftrightarrow\left(x+2\right)^3=0\)

\(\Leftrightarrow x+2=0\Leftrightarrow x=-2\)

21 tháng 8 2020

\(\frac{5}{6}x+\frac{1}{2}-\frac{1}{3}x=0,75x-\frac{7}{8}\)  

\(\frac{5}{6}x-\frac{1}{3}x-0,75x=-\frac{7}{8}-\frac{1}{2}\) 

\(\frac{5}{6}x-\frac{1}{3}x-\frac{3}{4}x=-\frac{11}{8}\) 

\(\frac{1}{2}x-\frac{3}{4}x=-\frac{11}{8}\)  

\(-\frac{1}{4}x=-\frac{11}{8}\)  

\(x=-\frac{11}{8}:-\frac{1}{4}\)  

\(x=\frac{11}{2}\)  

21 tháng 8 2020

Có:    \(\frac{x}{2}=\frac{y}{3}\)

=>   \(\frac{4x}{8}=\frac{3y}{9}=\frac{4x-3y}{8-9}=\frac{-2}{-1}=2\)

=>   \(\hept{\begin{cases}4x=16\\3y=18\end{cases}}\)

=>   \(\hept{\begin{cases}x=4\\y=6\end{cases}}\)

VC
21 tháng 8 2020

\(\frac{x}{2}=\frac{y}{3}\Leftrightarrow\frac{4x}{8}=\frac{3y}{9}\) và \(4x-3y=-2\)

Áp dụng tính chất dãy tỉ số bằng nhau, ta có : \(\frac{4x}{8}=\frac{3y}{9}=\frac{4x-3y}{8-9}=\frac{-2}{-1}=2\)

\(\Leftrightarrow4x=8.2=16\Leftrightarrow16\div4=4\)

\(\Leftrightarrow3y=2.9=18\Leftrightarrow y=18\div3=6\)

Vậy \(x=4;y=6\)

21 tháng 8 2020

\(3^2x22-3^3x19=3^2x22-3^2x3x19=3^2x\left(22-19x3\right)=9x\left(-35\right)=\left(-315\right)\)

21 tháng 8 2020

học tốt nhé!

21 tháng 8 2020

\(4\cdot5^2-\frac{81}{3^2}\) 

=\(4\cdot25-\frac{81}{9}\) 

= 100 - 9 

= 91 

21 tháng 8 2020

2^2×5^2-9^2:3^2

=(2×5-9:3)^2

=7^2

21 tháng 8 2020

x-2\(\frac{1}{4}\)=3\(\frac{1}{2}\)

x-\(\frac{9}{4}\)=\(\frac{7}{2}\)

x           =    \(\frac{7}{2}\)+\(\frac{9}{4}\)

x            = \(\frac{23}{4}\)

các câu còn lại, bạn tự làm nhé

21 tháng 8 2020

X - 2 1/4 = 3 1/2                    X + 2 3/4 = 5 2/3                    3 1/2 : X = 1 3/5                    X : 1 1/2 = 2 2/5                       

X -    9/4 =  7/2                      X +  11/4 = 17/3                        7/2 : X =   8/5                     X :    3/2  =   12/5

X            = 7/2 + 9/4              X             = 17/3 - 11/4                      X = 7/2 : 8/5               X             =  12/5 x 3/2

X            =     13/4                 X             =    35/12                           X = 35/16                   X             =   18/5

Nhớ tíck cho mik nha

Sai chỗ nào thì bảo mik 

21 tháng 8 2020

a) \(a^2+b^2+c^2=ab+bc+ac\)

\(\Leftrightarrow2\left(a^2+b^2+c^2\right)=2\left(ab+bc+ac\right)\)

\(\Leftrightarrow2a^2+2b^2+2c^2-2ab-2bc-2ac=0\)

\(\Leftrightarrow\left(a-b\right)^2+\left(c-a\right)^2+\left(b-c\right)^2=0\)

Ta có : \(\hept{\begin{cases}\left(a-b\right)^2\ge0\\\left(c-a\right)^2\ge0\\\left(b-c\right)^2\ge0\end{cases}}\)

\(\Rightarrow\left(a-b\right)^2+\left(c-a\right)^2+\left(b-c\right)^2=0\)

\(\Leftrightarrow a=b=c\)

21 tháng 8 2020

a. \(a^2+b^2+c^2=ab+bc+ca\)

\(\Leftrightarrow2a^2+2b^2+2c^2=2ab+2bc+2ca\)

\(\Leftrightarrow2a^2+2b^2+2c^2-2ab-2ab-2ca=0\)

\(\Leftrightarrow\left(a^2-2ab+b^2\right)+\left(b^2-2bc+c^2\right)+\left(c^2-2ca+a^2\right)=0\)

\(\Leftrightarrow\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2=0\)

\(\Leftrightarrow\hept{\begin{cases}a-b=0\\b-c=0\\c-a=0\end{cases}}\Leftrightarrow a=b=c\left(đpcm\right)\)

21 tháng 8 2020

5x2 - 5xy + 4y - 4x

= 5x ( x - y ) - 4 ( x - y )

= ( 5x - 4 ) ( x - y )

( x + y )3 + ( x - y )3

= 2x3 + 6xy2

= 2x ( x2 + 3y2 )

21 tháng 8 2020

5 x^2 - 5xy + 4y - 4x 

= 5x ( x - y ) - 4 ( x - y ) 

= ( x - y ) ( 5x - 4 ) 

( x + y )^3 + ( x - y )^3 

\(x^3+3x^2y+3xy^2+y^3+x^3-3x^2y+3xy^2-y^3\) 

\(2x^3+6xy^2\) 

=\(2x\left(x^2+3y^2\right)\) 

kết quả bằng -1.05169894